Calcium management challenges in a macrosomic child with subcutaneous fat necrosis. Issue 2 (19th February 2019) - Chan, Daniel; Salas-Walinsundin, Wilsie Martillano; Yap, Fabian Kok Peng; Koh, Mark Jean Aan
Abstract : We present a case that illustrates the fluctuations in calcium levels to be expected while managing an infant with maternal gestational diabetes mellitus who also develops subcutaneous fat necrosis (SCFN). There is initial hypocalcaemia due to functional hypoparathyroidism, requiring judicious calcium replacement. But with increased extrarenal production of 1, 25-dihydroxyvitamin D due to granulomatous inflammation of subcutaneous adipose tissue, hypercalcaemia ensues. With a self-limiting course, SCFN of the newborn has an excellent prognosis and resolves spontaneously. However, aberrations in serum calcium levels can manifest in life-threatening complications and must hence be closely monitored.